Analysis of drug disposal: a perspective of basic education students' knowledge (Research, Society and Development, 2023)
Worldwide, the consumption of medicines has been increasing, especially after the covid-19 pandemic,  consequently, there is a greater storage and disposal of medicines, however most people do not know the proper way to dispose of it. Therefore, it is necessary to raise awareness and sensitize the population in relation to correct disposal. This study aimed to survey the profile and prior knowledge of high school students from both public and private schools with regard to medication disposal. An exploratory and descriptive research methodology with a quantitative approach was used and the study took place in the city of Campina Grande - PB. Data were obtained by applying a questionnaire on Google Forms. The results obtained indicated that most families of public school students store their medicines in cabinets (48.1%) while families of private school students (42.4%) store them in a specific place for medicines. Regarding the other questions about the reading of the leaflet, drug expiration date, harmful effect on human health of expired medicine, disposing of medications, likely disposal site and if in your city you have already observed a disposal site, the highest percentages had the same response profile for both school systems, indicating that regardless of the school system, it is necessary to adopt the cross-cutting theme in the basic education curriculum in order to arouse students' interest and curiosity about the topic.